6-thioguanine inhibits EV71 replication by reducing BIRC3-mediated autophagy - Qiao You; Jing Wu; Ruining Lyu; Yurong Cai; Na Jiang; Ye Liu; Fang Zhang; Yating He; Deyan Chen; Zhiwei Wu (BMC Microbiology)
Abstract Background Enterovirus 71 (EV71) is one of the major causative agents of hand, foot, and mouth disease (HFMD), and can cause severe cerebral complications and even fatality in children younger than 5 years old. However, there is no specific medication for EV71 infection in clinical practice. Our previous studies had identified the 6-thioguanine (6-TG), an FDA-approved anticancer drug, as a potential antiviral agent, but its anti-EV71 activity is largely unknown, therefore, we aim to explore the antiviral effect of 6-TG on EV71. Results 6-TG significantly suppressed EV71 mRNA level, VP1 protein expression, and viral progeny production in HT-29 cells. In EV71-infected HT-29 cells, the 50% cytotoxicity concentration of 6-TG (CC50) was > 2000 µM and the 50% inhibitory concentration of 6-TG against EV71 (IC50) was 0.9302 µM. Interestingly, the selectivity index (SI) value of 6-TG against EV71 was > 2150.1, which was higher than the SI value (> 66.7) of ribavirin. Mechanistically, 6-TG treatment reduced the expression of baculoviral IAP repeat containing 3 (BIRC3), and further inhibited EV71 replication by attenuating BIRC3-mediated the complete autophagy. Conclusions 6-TG exerted a significant inhibitory effect on EV71 infection in vitro and prevented EV71-induced the complete autophagy by decreasing BIRC3 expression. Our work provided a basis for the further development of 6-TG as a therapy for EV71-associated HFMD.